1-D semi-analytical modeling and parametric study of a single phase rectangular Coupled Natural Circulation Loop. (2nd November 2019) - Dass, Akhil; Gedupudi, Sateesh
Highlights: 1-D semi-analytical modelling of a Coupled Natural Circulation Loop (CNCL) is proposed. The proposed 1-D model has been verified with a 3-D computational fluid dynamics study. Parameters considered include Grashof, Fourier and Stanton numbers and aspect ratio. Transient behaviour of horizontal CNCL has been found to be different from vertical CNCL. Abstract: The study of heat exchangers with both the hot and cold fluid sides driven by buoyancy forces is an area of considerable interest due to their inherent passivity and non-existence of moving parts. The current study aims to study such heat exchange devices employing the basic Coupled Natural Circulation Loop (CNCL) systems. A one dimensional (1-D) Fourier series based semi-analytical model of the basic CNCL system is proposed. A 3-D CFD validation is performed to validate the developed 1-D model. The non-dimensional numbers such as Grashof number, Fourier number, Stanton number and Reynolds number, which determine the system behavior are identified and a detailed parametric study is performed. Both vertical and horizontal CNCL systems are considered along with the parallel and counter flow configurations. The heater-cooler location greatly influences the behavior of CNCL system. The vertical CNCL always exhibits counter flow configuration whereas the horizontal CNCL system may exhibit parallel or counter flow arrangement depending on the heater-cooler location and initial flow conditions.